An innovative and integrated model for global outbreak response and research - a case study of the UK Public Health Rapid Support Team (UK-PHRST) - Philomena Raftery; Mazeda Hossain; Jennifer Palmer (BMC, 2021)
Abstract Background Despite considerable institutional experimentation at national and international levels in response to calls for global health security reform, there is little research on organisational models that address outbreak preparedness and response. Created in the aftermath of the 2013-16 West African Ebola epidemic, the United Kingdom's Public Health Rapid Support Team (UK-PHRST) was designed to address critical gaps in outbreak response illuminated during the epidemic, while leveraging existing UK institutional strengths. The partnership between the government agency, Public Health England, and an academic consortium, led by the London School of Hygiene and Tropical Medicine, seeks to integrate outbreak response, operational research and capacity building. We explored the design, establishment and early experiences of the UK-PHRST as one of the first bodies of its kind globally, paying particular attention to governance decisions which enabled them to address their complex mission. Methods We conducted a qualitative case study using 19 in-depth interviews with individuals knowledgeable about the team's design and implementation, review of organisational documents, and observations of meetings to analyse the UK-PHRST's creation, establishment and initial 2 years of operations. Results According to key informants, adopting a triple mandate (response, research and capacity building) established the team as novel in the global epidemic response architecture. Key governance decisions recognised as vital to the model included: structuring the team as a government-academic collaboration which leveraged long-term and complementary UK investments in public health and the higher education sector; adopting a more complex, dual reporting and funding structure to maintain an ethos of institutional balance between lead organisations; supporting a multidisciplinary team of experts to respond early in outbreaks for optimal impact; prioritising and funding epidemic research to influence response policy and practice; and ensuring the team's activities reinforced the existing global health architecture. Conclusion The UK-PHRST aims to enhance global outbreak response using an innovative and integrated model that capitalises on institutional strengths of the partnership. Insights suggest that despite adding complexity, integrating operational research through the government-academic collaboration contributed significant advantages. This promising model could be adopted and adapted by countries seeking to build similar outbreak response and research capacities.